EFFECTS OF REGIONAL AND TRANSREGIONAL PLAYERS’ POLICIES IN CONTINUATION OF TENSION BETWEEN IRAN AND AZERBAIJAN - Rad GOUDARZI, Masoumeh; Baei LASHAKI, Abdollah (CENTRAL ASIA AND THE CAUCASUS, 2013)
Iran and Azerbaijan are key countries in the Caspian Basin thanks to their historical continuity, religious and cultural similarities, shared energy resources, and strategic position. However, since Azerbaijan gained its independence, complex and contradictory interactions have been shaping their relations and influencing the region’s dynamics. At the initial stage, their relations were affected by political and ideological differences, as well as the sharp increase in the geopolitical importance of the Caucasus and the Caspian Basin in past two decades. Nor could the role of external factors be ignored. The formation of new borders and political blocs, as well as access to energy resources have made the region a focal point in world geopolitics and provided grounds for the intervention of regional and transregional powers aiming to attain their security, as well as their political and economic interests. This study examines security, as well as the political and economic factors at the internal and external levels that have contributed to escalation of the conflicts between Iran and Azerbaijan in the past two decades.